Gestational psittacosis: A case report and literature review. Issue 5 (19th February 2020) - Katsura, Daisuke; Tsuji, Shunichiro; Kimura, Fuminori; Tanaka, Tomoki; Eguchi, Yutaka; Murakami, Takashi
Abstract: Gestational psittacosis is a rare disease that is associated with significant maternal and fetal morbidity and mortality. Currently, there is no examination method which allows for a quick diagnosis. We report a case of gestational psittacosis that could not be diagnosed as psittacosis during treatment and resulted in maternal and fetal death despite intensive treatment. We also reviewed 23 cases of gestational psittacosis. Fetal and maternal mortality was 82.6% (19/23) and 8.7% (2/23), respectively. In pregnant women with high fever and flu‐like symptoms, we should suspect Chlamydia psittaci infection if at least one of the following is present; contact with sheep, parrots, parakeets or goats; normal or moderately decreased leucocyte count, thrombocytopenia and hepatic and/or renal dysfunction; cough and/or lobe consolidation or infiltration on chest X‐ray. Antibiotic therapy with macrolide prenatally, macrolide or tetracycline postnatally and termination of pregnancy should be considered.